Effects of dietary Bopu powder supplementation on intestinal development and microbiota in broiler chickens - Liu, Yang; Wang, Qinjin; Liu, Hua; Niu, Jiax‑ing; Jiao, Ning; Huang, Libo; Jiang, Shuzhen; Guan, Qinglin; Yang, Weiren; Li, Yang (Frontiers in Microbiology, 2022)
This study aimed to investigate the effect of dietary supplementation with Bopu powder on intestinal development and bacterial community composition in broiler chickens. A total of 486 1-day-old arbor acres broilers were fed a basal diet (CON group), a basal diet supplemented with 50 mg/kg aureomycin (AB group), or a basal diet supplemented with 40 mg/kg Bopu powder (BP group). The results showed that the BP group had significantly lower serum tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, and diamine oxidase concentrations and had significantly higher serum IL-10 concentrations than CON group (P < 0.05). Groups AB and BP had a significantly higher weight per unit length of the small intestine and villus height than the CON group (P < 0.05), and BP group had a significantly higher ratio of villus height to crypt depth than groups CON and AB (P < 0.05). Compared to the CON group, dietary Bopu powder or aureomycin supplementation significantly increased transforming growth factor-α concentration and mRNA expressions of zonula occludens-1 (ZO-1) and occludin, and decreased intestinal mucosal concentrations of TNF-α, IL-6, IL-10, caspase-3, and caspase-8 and mRNA expressions of nuclear factor-kappa- B and Bax/Bcl-2 ratio in the intestinal mucosa (P < 0.05). Meanwhile, BP group had significantly higher ZO-1, secretory immunoglobulin A, interferon-γ concentrations and mRNA expressions of glucose transporter type-2 and sirtuin-1, and significantly lower IL-1β concentration than groups CON and AB in intestinal mucosa (P < 0.05). Dietary Bopu powder supplementation significantly increased the concentration of trefoil factor family member and mRNA expressions of superoxide dismutase-1 and bcl-2 associated X, and significantly reduced casepase-9 concentration and myeloid differentiation primary response-88 expression in the intestinal mucosa of broiler chickens relative to CON group (P < 0.05). Moreover, results of high-throughput sequencing showed that broilers in the BP group had microbial community structure distinct from that in CON group, and the addition of Bopu powder increased the abundances of Faecalibacterium and Colidextribacter (P < 0.05). Therefore, our study suggests a synergic response of intestinal development and microbiota to the Bopu powder, and provides a theoretical basis as a potential substitute for antibiotics.